Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion with Emphasis on Minimizing CT to Recanalization Times (ESCAPE) Trial: Methodology. Issue 3 (April 2015) - Demchuk, Andrew M.; Goyal, Mayank; Menon, Bijoy K.; Eesa, Muneer; Ryckborst, Karla J.; Kamal, Noreen; Patil, Shivanand; Mishra, Sachin; Almekhlafi, Mohammed; Randhawa, Privia A.; Roy, Daniel; Willinsky, Robert; et al.
ESCAPE is a prospective, multicenter, randomized clinical trial that will enroll subjects with the following main inclusion criteria: less than 12 h from symptom onset, age > 18, baseline NIHSS >5, ASPECTS score of >5 and CTA evidence of carotid T/L or M1 segment MCA occlusion, and at least moderate collaterals by CTA. The trial will determine if endovascular treatment will result in higher rates of favorable outcome compared with standard medical therapy alone. Patient populations that are eligible include those receiving IV tPA, tPA ineligible and unwitnessed onset or wake up strokes with 12 h of last seen normal. The primary end-point, based on intention-to-treat criteria is the distribution of modified Rankin Scale scores at 90 days assessed using a proportional odds model. The projected maximum sample size is 500 subjects. Randomization is stratified under a minimization process using age, gender, baseline NIHSS, baseline ASPECTS (8–10 vs. 6–7), IV tPA treatment and occlusion location (ICA vs. MCA) as covariates. The study will have one formal interim analysis after 300 subjects have been accrued. Secondary end-points at 90 days include the following: mRS 0–1; mRS 0–2; Barthel 95–100, EuroQOL and a cognitive battery. Safety outcomes are symptomatic ICH, major bleeding, contrast nephropathy, total radiation dose, malignant MCA infarction, hemicraniectomy and mortality at 90 days.